2022
DOI: 10.3390/cli10100137
|View full text |Cite
|
Sign up to set email alerts
|

Intensity, Duration and Spatial Coverage of Aridity during Meteorological Drought Years over Northeast Thailand

Abstract: Gaps in drought monitoring result in insufficient preparation measures for vulnerable areas. This paper employed the standardized precipitation index (SPI) to identify meteorological drought years and the Thornthwaite aridity index (TAI) to evaluate aridity in three provinces of northeast Thailand growing cassava and sugarcane at massive scales. Precipitation and temperature data were sourced from Global Land Data Assimilation System-2 (GLDAS-2) Noah Model products at 0.25 degree resolution and used for calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…That is, water could not be used for meeting the water demands after the rainy season, as shown in Figures 18-20. These conditions depict a drought situation as faced in the lowest rainfall year according to historic records for the northeast region of Thailand [39] The reservation volume in the case of the lowest rainfall after the rainy season (November) was lower than the lowest reservation volume. That is, water could not be used for meeting the water demands after the rainy season, as shown in Figures 18-20.…”
Section: Water Demandsmentioning
confidence: 81%
See 1 more Smart Citation
“…That is, water could not be used for meeting the water demands after the rainy season, as shown in Figures 18-20. These conditions depict a drought situation as faced in the lowest rainfall year according to historic records for the northeast region of Thailand [39] The reservation volume in the case of the lowest rainfall after the rainy season (November) was lower than the lowest reservation volume. That is, water could not be used for meeting the water demands after the rainy season, as shown in Figures 18-20.…”
Section: Water Demandsmentioning
confidence: 81%
“…That is, water could not be used for meeting the water demands after the rainy season, as shown in Figures 18-20. These conditions depict a drought situation as faced in the lowest rainfall year according to historic records for the northeast region of Thailand [39]…”
Section: Water Demandsmentioning
confidence: 98%
“…Additionally, research has suggested that longan trees may be vulnerable to drought during critical stages such as flowering and early fruit development [69]. Thailand faced a devastating drought from November 2009 to August 2010, with temperatures exceeding 40 • C; in addition, between 2015 and 2016, one of the worst droughts in decades caused critically low water levels in reservoirs, mainly affecting central and northeastern areas [70].…”
Section: Discussionmentioning
confidence: 99%